2016
DOI: 10.1542/peds.2015-2413
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Care Gaps in Adolescents With Complex Chronic Condition Transitioning to Adulthood

Abstract: CONTEXT: Breaks in the delivery of health care (ie, [health]care gaps) occur in a large proportion of young people transitioning to adulthood. Developing interventions that prevent adolescents from dropping out of the medical system, as they leave pediatric care, requires an understanding of determinants of care gaps. OBJECTIVE:To ascertain determinants of care gaps in young people with chronic conditions as they transition to adulthood by performing a systematic literature search.DATA SOURCES: MEDLINE, CINAHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 42 publications
5
57
1
1
Order By: Relevance
“…This suggests that, in our cohort, disease severity leading to hospitalization may negatively influence transition outcomes. In contrast, other studies in SCD and other chronic diseases found milder disease and decreased health care utilization correlated with increased care gaps . Thus, while co‐morbidities and disease severity are related to adverse health outcomes during transition, disease‐related characteristics and use of health care services are variably linked to transition outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, in our cohort, disease severity leading to hospitalization may negatively influence transition outcomes. In contrast, other studies in SCD and other chronic diseases found milder disease and decreased health care utilization correlated with increased care gaps . Thus, while co‐morbidities and disease severity are related to adverse health outcomes during transition, disease‐related characteristics and use of health care services are variably linked to transition outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…| 381 typical example of a chronic childhood condition. It is the most common congenital malformation with a birth prevalence of up to 9.3 cases/1,000 newborns (van der Linde et al, 2011) and in many cases it requires lifelong medical follow-up (Goossens, Bovijn, Gewillig, Budts, & Moons, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Empowering the patient/family though interactive conversation, and simulation-based training will effectively support the young patient in problem-solving; merely providing answers to prepared questions or suggesting ready solutions through the physician disease glance will not support increased retention of knowledge and skills. 3,4,15,25,29,33 Barriers to good compliance can be attributed to the lack or misunderstanding of the AID nature and disease prioritizations, any adverse events, the AID impact in socializing or relationships, as well as parenteral administration of biologics. Poor compliance to these agents may not just be fear of needles, but reluctance of difficulties with self-administration, that my lead to social isolation.…”
Section: Avoiding Barriers Of a Successful Transition (The Waves)mentioning
confidence: 99%
“…25,26,32 Icarus' wings Icarus' contemporary flight wings are the growing skills for communication, decision making, and self-health management, aiming towards a healthy life-style and realization of the life-long co-existence with the AID. 25,32,33 Compliance to medication -even if parenterally administered -is of high importance to "pilot" the safe flight. 34 When is the ideal onset time for the "flight preparation"?…”
mentioning
confidence: 99%